Seasonal variations affect the ecosystem functioning and microbial assembly processes in plantation forest soils - Wang, Min; Masoudi, Abolfazl; Wang, Can; Zhao, Liqiang; Yang, Jia; Yu, Zhijun; Liu, Jingze (Frontiers in Microbiology, 2024)
While afforestation mitigates climate concerns, the impact of afforestation on ecological assembly processes and multiple soil functions (multifunctionality) in afforested areas remains unclear. The Xiong'an New Area plantation forests (Pinus and Sophora forests) in North China were selected to examine the effects of plantation types across four distinct seasons on soil microbiomes. Three functional categories (nutrient stocks, organic matter decomposition, and microbial functional genes) of multifunctionality and the average (net) multifunctionality were quantified. All these categories are directly related to soil functions. The results showed that net soil multifunctionality as a broad function did not change seasonally, unlike other narrow functional categories. Bacterial communities were deterministically (variable selection and homogenous selection) structured, whereas the stochastic process of dispersal limitation was mainly responsible for the assembly and turnover of fungal and protist communities. In Pinus forests, winter initiates a sudden shift from deterministic to stochastic processes in bacterial community assembly, accompanied by decreased Shannon diversity and heightened nutrient cycling (nutrient stocks and organic matter decomposition). This indicates the potential vulnerability of deterministic assembly to seasonal fluctuations, particularly in environments rich in nutrients. The results predicted that protist community composition was uniquely structured with C-related functional activities relative to bacterial and fungal β-diversity variations, which were mostly explained by seasonal variations. Our study highlighted the importance of the protist phagocytosis process on soil microbial interactions through the predicted impact of protist α-diversity on microbial cooccurrence network parameters. This association might be driven by the high abundance of protist consumers as the main predators of bacterial and fungal lineages in our sampling plots. Our findings reveal that the complexity of microbial co-occurrence interactions was considerably higher in spring, perhaps attributing thermal variability and increased resource availability within spring that foster microbial diversity and network complexity. This study contributes to local ecosystem prospects to model the behavior of soil biota seasonally and their implied effects on soil functioning and microbial assembly processes, which will benefit global-scale afforestation programs by promoting novel, precise, and rational plantation forests for future environmental sustainability and self-sufficiency.